Development of enteric coated sustained release minitablets containing mesalamine - Dayse Fernanda de Souza; Karin Goebel; Itamar Francisco Andreazza (Universidade de São Paulo, 2013)
The aim of this study was to develop and evaluate a multiparticulate modified release system, composed of minitablets with a sustained release matrix system coated with a pH-dependent release polymer, using mesalamine as a model drug. Polyox® WSR 1105 was the polymer used in the matrix system and Eudragit® L30D55 was used as a pH-dependent polymer. The minitablets (with 20%, 30% or 40% Polyox® concentration) were prepared by dry granulation, which led to good quality minitablets. The developed minitablets were coated in a fluidized bed at 8% of the coating level. Dissolution studies were performed in media that simulated the gastrointestinal tract (pH 1.4, 6.0 and 7.2) and showed that formulations with higher Polyox® concentrations were capable of retaining the drug release in pH 1.4. All formulations prolonged the drug release and presented zero-order kinetic behaviour. The Korsmeyer-Peppas model demonstrated that formulations with 20% or 30% of polymer exhibited anomalous transport behaviour, whilst the 40% sample exhibited super case II model transportation. Dissolution efficiency showed that only the formulations containing 20% and 40% polymer could be considered statistically different.